CONDITIONS AND FACTORS OF THE FORMATION OF THE BUKHARA PEOPLE'S SOVIET REPUBLIC (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article provides a comprehensive analysis of the historical, political, and social factors that led to the formation of the Bukhara People's Soviet Republic. It explores the crisis within the Bukhara Emirate, the reformist activities of the Jadid movement, Soviet Russia’s geopolitical interests, and the revolutionary changes of 1917–1920. Key events such as the Kolesov campaign, the Qiziltepa agreement, the 1920 uprising, and the formation of the BPSR are discussed step by step with objective conclusions based on historical sources. The BPSR serves as a model for transitional processes in Central Asia.